The Functional Trajectory in Frail Compared With Non-frail Critically Ill Patients During the Hospital Stay - Fuest, K. E.; Lorenz, Marco; Grunow, Julius J.; Weiss, Björn; Mörgeli, Rudolf; Finkenzeller, Sebastian; Bogdanski, Ralph; Heim, Markus; Kapfer, Barbara; Kriescher, Silja; Lingg, Charlotte; Martin, Jan; et al. (Frontiers in Medicine, 2021)
Background: Long-term outcome is determined not only by the acute critical illness but increasingly by the reduced functional reserve of pre-existing frailty. The patients with frailty currently account for one-third of the critically ill, resulting in higher mortality. There is evidence of how frailty affects the intrahospital functional trajectory of critically ill patients since prehospital status is often missing. Methods: In this prospective single-center cohort study at two interdisciplinary intensive care units (ICUs) at a university hospital in Germany, the frailty was assessed using the Clinical Frailty Scale (CFS) in the adult patients with critical illness with an ICU stay >24 h. The functional status was assessed using the sum of the subdomains “Mobility” and “Transfer” of the Barthel Index (MTB) at three time points (pre-hospital, ICU discharge, and hospital discharge). Results: We included 1,172 patients with a median age of 75 years, of which 290 patients (25%) were frail. In a propensity score-matched cohort, the probability of MTB deterioration till hospital discharge did not differ in the patients with frailty (odds ratio (OR) 1.3 [95% CI 0.8–1.9], p = 0.301), confirmed in several sensitivity analyses in all the patients and survivors only. Conclusion: The patients with frailty have a reduced functional status. Their intrahospital functional trajectory, however, was not worse than those in non-frail patients, suggesting a rehabilitation potential of function in critically ill patients with frailty.